Self-perception of physical fitness, functionality and quality of life in university students - Tuillang Alexander Yuing; Claudio Soto-Espíndola; Nathalie Andrea Valdés-Valdés; Guillermo Méndez-Rebolledo; Eduardo Guzmán-Muñoz (Revista Cubana de Medicina Militar)
Introduction: University life is a stage that imposes a series of changes that can lead to the acquisition of unhealthy lifestyles with a negative impact on the quality of life. Objective: To compare the self-perception of physical fitness, functionality and quality of life, level of physical activity and sedentary behavior in university students. Methods: The study is descriptive, cross-sectional and observational in design. 566 university students were selected through stratified random sampling. The level of physical activity was measured through the short version of the International Physical Activity Questionnaire, physical fitness was determined through the self-report International Fitness Scale, the functionality of upper limbs was measured through the Self-Assessment Questionnaire. -Report Disabilities of Arm, Shoulder and Hand, the functionality of the lower limbs was used with the Lower Extremity Functional Scale Questionnaire and the perception of quality of life with the SF-36 health questionnaire. Results: the physically active participants perceived a better general physical condition (p = 0.001), cardiorespiratory condition (p = 0.001), muscular strength (p = 0.001), speed / agility (p = 0.001) and greater functionality of lower limbs (p = 0.001) than the group of physically inactive participants. Similar results were obtained when comparing the perception of physical condition and functionality according to sedentary behavior. In relation to the perception of quality of life according to the level of physical activity and sedentary behavior, they agreed that both the physically active and the non-sedentary had better indicators of general and mental health. Conclusion: The physically active and non-sedentary individuals present a better self-perception of physical condition, functionality and quality of life compared to their physically inactive and sedentary peers.